Accarezzare le rughe della terra: l’associazione “Le terre traverse” tra la via Emilia e il Po - Danani, Carla (Scienze del Territorio, 2014)
This reflective piece aims to recount the experience taking place in a corner of the Po Valley, between via Emilia and the Po river: fifteen farms have joined together and created an association to enhance the material and immaterial culture of the rural world. For four years now, Le Terre Traverse has been organising cultural events in farmhouses enhancing the architecture of the landscape and within the landscape. Over time, members have become more self-aware and they have offered their contribution to social cohesion: they claimed a valuable social capital, with no inferiority towards urban life. On behalf of those whose livelihood depends on the land, theatre, music, exhibitions and conferences have been organized on real open-air sets in order to convey the importance of and enhance the value of the land. The association can be followed on its Facebook page: look for Terre Traverse.